Evaluation of Real Estate Development Process in Sharia Housing Based on The Application of The Ideal Islamic Housing Concept - Perdana, Angga; Setijanti, Purwanita; Cahyadini, Sarah (IPTEK Journal of Proceedings Series, 2020)
The ideal Islamic housing concept should implement Islamic values holistically in the sharia housing project. The development process of sharia housing looks at housing as not merely a product but also implements shari’ah marketing methods and opens up opportunities for sharia investment in housing finance. Sharia housing with an ideal Islamic housing concept accommodates sharia values in various stages of development, starting from the initial idea formation, feasibility studies, planning and design, funding schemes, employment contracts, marketing selling and buying methods, to estate management. In housing development, the role of investors is important to control the quality of a product that is being developed. A case study strategy was used, with descriptive statistical analysis in evaluating the development process of the Islamic housing concept. Medina Residence 1 was taken as the case study based on their promotion in which they applied the Islamic housing concept in the development process. The evaluation result of the application Islamic housing concept in the development process at Medina Residence 1, shows that the Islamic housing concept has been applied and received a very satisfying response from investors. Therefore, sharia housing developers need to pay attention to it to implement Islamic value in housing development holistically.